Comparison of biochemical markers and technetium 99m methoxyisobutylisonitrile imaging in primary and secondary hyperparathyroidism - Wang, Yuhua; Liu, Ye; Li, Na; Zhang, Wanchun (Frontiers in Endocrinology, 2023)
Objective: To investigate the differences in biochemical marker levels and the extent of lesion visualization on technetium 99m methoxyisobutylisonitrile (99mTc-MIBI) imaging between primary hyperparathyroidism (PHPT) and secondary hyperparathyroidism (SHPT). Methods: Nineteen patients with PHPT and 14 patients with SHPT were enrolled in the study, all of whom underwent routine 99mTc-MIBI dual-phase planar imaging, single-photon emission computed tomography combined with computed tomography (SPECT/CT fusion) imaging, and serum biochemical and hormonal investigations prior to surgery. The target-to-non-target (T/NT) ratios were calculated based on images from the early and delayed phases of 99mTc-MIBI planar imaging and also based on SPECT/CT fusion imaging. The volume of the parathyroid glands was measured following their excision. Results: A total of 62 parathyroid glands were removed: 14 parathyroid adenomas and five parathyroid carcinomas in PHPT patients; and 18 parathyroid adenomas, 17 parathyroid hyperplasia lesions, and eight instances of nodular hyperplasia with adenoma in SHPT patients. The median volume of the lesions in PHPT and SHPT was 1.69 cm3 and 0.52 cm3 respectively, and the difference between them was statistically significant (P = 0.001). The median T/NT ratios calculated at the early phase of 99mTc-MIBI planar imaging, the delayed phase of 99mTc-MIBI planar imaging, and the subsequent SPECT/CT fusion imaging were 1.51, 1.34, and 2.75, respectively, in PHPT, and 1.46, 1.30, and 1.38, in SHPT, respectively. The T/NT ratio difference between PHPT and SHPT on the SPECT/CT fusion imaging was statistically significant (P = 0.002). The histopathology subtypes of the lesions were associated with significant differences in two areas: the T/NT ratios on the SPECT/CT fusion imaging and the volume of the lesions (P=0.002, P<0.001). Conclusion: The proportion of positive findings on 99mTc-MIBI dual-phase planar imaging and the T/NT ratios of 99mTc-MIBI SPECT/CT fusion imaging were higher in PHPT than in SHPT. The volume of parathyroid lesions in SHPT was smaller than in PHPT.